Correlation of Arm Strength, Handling, and Flexibility Coordination of Forehand Drive Skills - Rizki Ridha Kusuma (STKIP Muhammadiyah Kuningan, 2019)
Playing badminton is a game that is often performed by most people in all walks of life, for techniques in playing badminton must be mastered including forehand drives which in doing this technique many elements of the body are involved so we need to know how strong the body parts are involved is to find out the relationship between each variable of arm muscle strength, hand-eye coordination and flexibility towards forehand drive skills. The research method used in this study is a quantitative approach, a survey method with measurement techniques and tests, while the analysis technique uses a correlation analysis approach. The results of this study after statistical testing of empirical data obtained from the field can be said that the three independent variables proposed namely arm muscle strength, eye-hand coordination and flexibility significantly positively correlated with forehand drive skills in Bogor badminton club athletes.